Computational studies of a series of closely related acenaphthopyrazine derivative - Rebaz Anwar Omer; Rebaz Obaid Kareem; Yousif Hussein Azeez; Lana Omer Ahmed; Damir A. Safin; karukh Ali Babakr (Results in Surfaces and Interfaces)
The novelty of the study is in the use of quantum computing analysis of acenaphthopyrazine derivatives using Density Functional Theory (DFT) with the B3LYP/6-31G(d,p) basis set. The research focused on intramolecular charge transfer (ICT) and its influence on non-linear optical (NLO) properties. The NLO analysis revealed that the protonated forms of these compounds exhibit higher dipole moments, indicating their potential for NLO applications. Natural Bond Orbital (NBO) analysis identified molecule 5 as having the highest E(2) value of 509.41 kcal/mol, signifying strong electron donation from nitrogen to hydrogen atoms. The study also evaluated the thermal properties, showing that the Gibbs free energy remained positive across a wide temperature range, suggesting that none of the compounds are spontaneously formed in either neutral or protonated states. Additionally, Monte Carlo simulations indicated favorable adsorption energies for these derivatives on the Fe (110) surface, with compound 5 demonstrating the most significant inhibitory potential. We conduced of that, lower negative adsorption energy (−216.729) compound 1 are confirm with highest energy gap (3.396 eV), and smaller refractive index, and electrical conductivityof compound 1 indicates a small metal-inhibitor molecule interaction, as well as are agreement with Monte Carlo simulation for adsorption on Fe (110) non protonated case.